Meta-analysis of TSH suppression therapy and the risk of cardiovascular events after thyroid cancer surgery - Yang, Xiao; Guo, Nan; Gao, Xin; Liang, Jiwang; Fan, Xinlong; Zhao, Yuejiao (Frontiers in Endocrinology, 2022)
Objective To investigate the relationship between TSH suppression therapy and cardiovascular events in patients with thyroid cancer after surgery. Methods Pub Med, Web of Science, and Embase databases were retrieved to collect studies related to the risk of cardiovascular events in patients treated with TSH suppression after thyroid cancer surgery. RevMan statistical software was used for meta-analysis. Results A total of 14 studies were included. The mean heart rate of patients after thyroid cancer surgery was higher than that of the control group (SMD=2.59, 95% CI: -0.37,.54), and the risk of atrial fibrillation was increased compared with the control group (RR = 1.52, 95%CI, 1.28-1.81; I = 63%). Ejection fraction and left ventricular end-diastolic diameter were not significantly different between the two groups, ejection fraction SMD = -0.10, 95% CI: -3.73, 3.52, left ventricular end-diastolic diameter SMD = -0.09, 95% CI: - 1.29, 1.11. Patients with TSH suppression after thyroid cancer had higher mean systolic blood pressure than controls (SMD = 1.97, 95% CI: −1.09, 5.03) and mean diastolic blood pressure (SMD = 1.85, 95% CI: -0.15, 3.85). Conclusion Meta-analysis concluded that TSH suppression therapy after thyroid cancer surgery increases the risk of atrial fibrillation in patients. In addition, the heart rate, systolic blood pressure and diastolic blood pressure are higher than those in the control group, and there is no significant difference in ejection fraction and left ventricular end-diastolic diameter.